Leading names in education: Jean-Fréderic Oberlin (Journal of Parents and Teachers, 2013)
Jean Fréderic Oberlin was a rural teacher and later forerunner of the first public library as well as creator of Kindergartens. He specialised in making up rural schools and grouping them into small areas. On the other hand, this great teacher is also known by the creation of places devoted to the care and education of orphans.
Keywords: Leading names in education; Jean Fréderic Oberlin; teacher; orphans; kindergartens; education